The effect of football practice duration on improving the balancing skills of football players with hearing impairments - Sobyanin F.I.; Zavalishina S.Yu.; Kachenkova E.S.; Bobkova S.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The present study is aimed at determining the possibilities of maintaining balance in people with hearing impairments who practice in the specialized football section. Methods and structure of the study. As part of the study, a group of 36 hard-of-hearing second-year university students who regularly attend adaptive soccer training sessions were monitored. Distribution by length of service: 12 people – one year, 10 people – two years and 14 people – three years. The control group consisted of 12 somatically healthy, hard-of-hearing second-year students who did not exercise. The ability to maintain balance was assessed using the Stabilan 01-2 device before and after physical exertion. Statistical data processing was carried out using the Student’s t-test. Results and conclusions. The results showed that hearing-impaired young men playing football had a reduced ability to maintain balance as fatigue set in. The level of development of this indicator in hearing-impaired athletes increased with an increase in their training experience. The best results were recorded in football players with three years of experience, which is explained by the higher level of fitness of their muscular and vestibular systems.